Cleanliness and culture: Indonesian histories - Dijk van, Kees (Verhandelingen van het Koninklĳk Instituut voor Taal-, Land- en Volkenkunde, 2011)
Recent years have shown an increase in interest in the study of cleanliness from a historical and sociological perspective. Many of such studies on bathing and washing, on keeping the body and the streets clean, and on filth and the combat of dirt, focus on Europe. In Cleanliness and culture attention shifts to the tropics, to Indonesia, in colonial times as well as in the present. Subjects range from the use of soap and the washing of clothes as a pretext to claim superiority of race and class to how references to being clean played a role in a campaign against European homosexuals in the Netherlands Indies at the end of the 1930s. Other topics are eerie skin diseases and the sanitary measures to eliminate them, and how misconceptions about lack of hygiene as the cause of illness hampered the finding of a cure. Attention is also drawn to differences in attitude towards performing personal body functions outdoors and retreating to the privacy of the bathroom, to traditional bathing ritual and to the modern tropical Spa culture as a manifestation of a New Asian lifestyle. With contributions by Bart Barendregt, Marieke Bloembergen, Kees van Dijk, Mary Somers Heidhues, David Henley, George Quinn, and Jean Gelman Taylor.